Vascular function in kidney transplant recipients and in patients with renovascular disease - Päivärinta, Johanna (fi=Turun yliopisto|en=University of Turku|, 2021)
Cardiovascular mortality is 20 times higher in patients with chronic kidney disease and 3─5 times higher in patients with a kidney transplant than in the age-matched general population, which is partly explained by endothelial dysfunction. Endothelial function is pivotal in the pathogenesis of coronary artery disease, kidney allograft failure and atherosclerotic renovascular disease. In this study, our aim was to measure the myocardial perfusion reserve of patients with a kidney transplant with positron emission tomography (PET), which is the gold standard for measuring myocardial perfusion. Secondly, the aim was to test PET for evaluation of kidney perfusion in patients with a kidney transplant and to examine if early kidney perfusion predicts renal histology at one year after transplantation. In addition, our aim was to measure renal flow reserve by PET in patients with atherosclerotic renovascular disease. The results were compared to those of the healthy controls. The myocardial perfusion reserve was similar in patients and in healthy controls after correction for cardiac workload. Renal cortical perfusion was decreased in kidney transplant recipients compared with healthy control subjects. Allograft perfusion assessed early after transplantation did not predict renal fibrosis 12 months after transplantation. The renal flow reserve was small and highly variable both in patients with atherosclerotic renovascular disease and in healthy controls. The myocardial perfusion reserve is well preserved in patients with a kidney transplant. PET is an adequate method for evaluation of renal perfusion in patients with a kidney transplant, but not for prediction of renal fibrosis one year after transplantation. The decreased renal cortical perfusion in kidney transplant recipients is probably explained by microcircular and endothelial dysfunction of the allograft. The renal flow reserve was modest, which makes the value of this variable questionable for prognosticating the response to revascularisation in renovascular disease.

Vaskulaarifunktio munuaissiirron saaneilla sekä renovaskulaaritautia sairastavilla potilailla Sydän- ja verisuonitautikuolleisuus on 20 kertaa suurempi kroonista munuaisten vajaatoimintaa sairastavilla ja 3-5 kertaa suurempi munuaissiirteen saaneilla potilailla kuin ikävakioidulla muulla väestöllä. Tämän katsotaan selittyvän osin verisuonten sisäkalvon eli endoteelin toiminnan häiriöllä. Endoteelin toiminnalla on keskeinen asema sepelvaltimotaudin, munuaissiirteen toiminnan heikkenemisen ja renovaskulaaritaudin patofysiologiassa. Tämän tutkimuksen tavoitteena oli määrittää munuaissiirtopotilaiden sepelvaltimoiden virtausreservi kvantitatiivisella positroniemissiotomografialla (PET), joka on sepelvaltimoiden verenvirtauksen eli sepelvaltimoperfuusion arvioinnin kultainen standardi. Tavoitteena oli myös selvittää PET-tutkimuksen toimivuus munuaissiirteen perfuusion mittauksessa. Tutkimuksella pyrittiin lisäksi selvittämään, ennustaako varhainen munuaissiirteen perfuusio munuaissiirteen histologiaa vuoden kohdalla siirrosta. Viimeisenä tavoitteena oli selvittää PETtutkimuksella munuaisen virtausreservi renovaskulaaritautia sairastavilla potilailla. Sepelvaltimoiden virtausreservi oli yhtä suuri munuaissiirtopotilailla ja terveillä, kun sydämen työkuorma otettiin huomioon. Sen sijaan munuaisperfuusio oli heikentynyt siirtopotilailla verrattuna terveisiin. Varhain munuaissiirron jälkeen määritetty munuaisperfuusio ei ennustanut siirteen histologiaa vuoden kohdalla siirrosta. Munuaisen virtausreservi oli pieni ja arvot vaihtelevia sekä ateroskleroottista munuaissairautta sairastavilla potilailla että terveillä verrokeilla. Sepelvaltimoiden virtausreservi on hyvin säilynyt munuaissiirtopotilailla. PET on käypä metodi munuaissiirteen perfuusion mittauksessa, mutta se ei ennusta siirteen fibroosia vuoden kuluttua siirrosta. Munuaisperfuusion väheneminen siirtopotilailla selittynee mikrosirkulaation ja endoteelin toiminnan häiriöllä. Munuaisen virtausreservin pieni koko kyseenalaistaa sen käytön munuaisvaltimoahtauman laajennusvasteen ennustajana.